Periodic solutions of second-order neutral functional differential systems with time-varying operator and delays - Zhengxin Wang; Shiping Lu; Jinde Cao (Нелінійні коливання, 2014)
This paper aims to investigate the existence of periodic solutions for second-order neutral functional differential systems with time-varying operator and delays. The interesting issue is that the coefficient matrix of the neutral difference operator is not a constant matrix, which is different from the other literature. Some properties of the time-varying neutral difference operator and the results on the existence of periodic solutions of second-order neutral functional differential systems are obtained. Moreover, a numerical simulation is given to illustrate the theoretical results. Дослiджується iснування перiодичних розв’язкiв функцiонально-диференцiальних систем другого порядку з залежним вiд часу оператором та запiзненнями. При цьому матриця коефiцiєнтiв нейтрального рiзницевого оператора не є сталою на вiдмiну вiд випадкiв, описаних у лiтературi. Отримано деякi властивостi нейтрального змiнного за часом рiзницевого оператора та результати щодо iснування перiодичних розв’язкiв нейтральних функцiональнодиференцiальних систем другого порядку. Наведено числовий приклад для iлюстрацiї теоретичних результатiв.